Electronic cigarettes: A position statement from the Thoracic Society of Australia and New Zealand* - McDonald, C.F.; Jones, S.; Beckert, L.; Bonevski, B.; Buchanan, T.; Bozier, J.; Carson-Chahhoud, K.V.; Chapman, D.G.; Dobler, C.C.; Foster, J.M.; Hamor, P.; Hodge, S.; et al. (2020)
The TSANZ develops position statements where insufficient data exist to write formal clinical guidelines. In 2018, the TSANZ addressed the question of potential benefits and health impacts of electronic cigarettes (EC). The working party included groups focused on health impacts, smoking cessation, youth issues and priority populations. The 2018 report on the Public Health Consequences of E-Cigarettes from the United States NASEM was accepted as reflective of evidence to mid-2017. A search for papers subsequently published in peer-reviewed journals was conducted in August 2018. A small number of robust and important papers published until March 2019 were also identified and included. Groups identified studies that extended, modified or contradicted the NASEM report. A total of 3793 papers were identified and reviewed, with summaries and draft position statements developed and presented to TSANZ membership in April 2019. After feedback from members and external reviewers, a collection of position statements was finalized in December 2019. EC have adverse lung effects and harmful effects of long-term use are unknown. EC are unsuitable consumer products for recreational use, part-substitution for smoking or long-term exclusive use by former smokers. Smokers who require support to quit smoking should be directed towards approved medication in conjunction with behavioural support as having the strongest evidence for efficacy and safety. No specific EC product can be recommended as effective and safe for smoking cessation. Smoking cessation claims in relation to EC should be assessed by established regulators.